The critical terminology between the successful past and present crisis - Cherouana, Moussa; Saaiud, Fouzia (Milev Journal of Research and Studies, 2018)
The richess of the Arabic language from scientific terminology has the peculiarity of the past and the present. Its terms were a container for the terminology of the various sciences, where the ancients of critics and philosophers were aware of its great importance. The critical term was a force attributed to the energies of the expressive language that enabled it to assimilate the cultures of other nations, such as persians, greecs, Indians and the Romans. From this point of view, our attention came to the Arabic critical term, trying to identify how it controls knowledge and reporting, and the extent of the ability of those working in this field to control the meanings of language functions. Because of their effects on the general intellectual aspects. So what is the reality of the Arabic critical term in this era? And why this retreat, this degragation and crisis?